Structures and thermal behaviour of some monooxalato and dioxalato metal complexes - Bacsa, John (Rhodes University, Faculty of Science, Department of Chemistry, 1996)
The crystal structure of Ba [Cu(Câ‚‚0â‚„)â‚‚(Hâ‚‚O)].5Hâ‚‚O has been determined using single crystal X-ray diffractometry. It crystallises in the triclinic system, space group PÄ« , with a = 6.539(2) Ã…, b = 9.211(3) Ã…, c = 10.928(3) Ã…, a = 85.42(3)Â°, Î² = 79.22(3)Â° , Î³ = 80.30(3)Â°, V = 636.08(8)Ã…Â³ and Z = 2. The structure consists of [Cu(Câ‚‚0â‚„)â‚‚(Hâ‚‚O)]Â²â » ions weakly bridged by barium ions and water molecules. The copper(II) ions are in a tetragonally elongated square-pyramidal environment with some trigonal distortion. The two oxalate groups occupy the equatorial positions and a water molecule occupies the axial position. The barium ion is surrounded by nine oxygens: five oxygens from water molecules and four oxygens from oxalate groups. The thermal behaviour of Ba [Cu(Câ‚‚0â‚„)â‚‚(Hâ‚‚O)].5Hâ‚‚0 in Nâ‚‚ has been examined using thermogravimetry (TG) and differential scanning calorimetry (DSC). The dehydration starts at relatively low temperatures (~80Â°C), but continues until the onset of the decomposition (~280Â°C). The decomposition takes place in two major stages. The mass of the intermediate after the first stage corresponded to the formation of barium oxalate and copper metal and, after the second stage, to the formation of barium carbonate and copper metal. The enthalpy for the dehydration was found to be 311 Â±30 kJ molâ »Â¹. The overall enthalpy change for the decomposition of Ba[Cu(Câ‚‚0â‚„)â‚‚]in Nâ‚‚ was estimated from the combined area of the peaks of the DSC curve as -347 kJ molâ »Â¹. The kinetics of the thermal dehydration and decomposition were studied using isothermal TG. The dehydration was strongly deceleratory and the Î±-time curves could be described by the three-dimensional diffusion (D3) model. The values of the activation energy and the pre-exponential factor for the dehydration were 125 Â±4 kJ molâ »Â¹ and (1.38 Â±0.08)x10Â¹â µ minâ »Â¹, respectively. The decomposition was complex, consisting of at least two concurrent processes. The decomposition was analysed in terms of two overlapping deceleratory processes. One process was fast and could be described by the contracting-geometry model with n = 5. The other process was slow and could also be described by the contracting-geometry model , but with n = 2. The values of Eâ‚ and A were 206 Â±23 kJ molâ »Â¹ and (2.2 Â±O.5)xl0Â¹â ¹minâ »Â¹, respectively, for the fast process, and 259 Â±37 kJ molâ »Â¹ and (6.3 Â±1.8)x10Â²Â³minâ »Â¹, respectively, for the slow process.The crystal structure of zinc oxalate dihydrate ([Zn(Câ‚‚0â‚„)(Hâ‚‚O)â‚‚]n) has also been determined by X-ray diffraction methods. It crystallises in the monoclinic system, space group C2/c with a = 11.786(2) Ã…, b = 5.397(1)Ã…, c = 9.712(1) Ã…, B = 126.19(5)Â°, V = 498.58(8)Ã…Â³, Z = 4 and R = 0.037 for 435 absorption-corrected independent reflections and 50 parameters. The asymmetric unit consists of half the monomeric unit [Zn(Câ‚‚0â‚„)(Hâ‚‚O)â‚‚). The structure consists of infinite, linear chains of zinc ions bridged by oxalate groups. The geometry of the coordination polyhedron surrounding the zinc ion is octahedral, with the oxalate oxygens occupying the equatorial positions and water molecules occupying the axial positions.
Keywords: Oxalates -- Research; Crystallography -- Research; Chemistry, Inorganic -- Research